Fair and efficient network congestion control algorithm based on minority game with local information - Zu-xi WANG; Zhao-zhang DENG; Li LI (Tongxin xuebao)
Low link utility,RTT unfairness and unfairness of Multi-Bottleneck network are the existing problems in the present network congestion control algorithms at large.Considering the local information of network,a congestion control model based on minority game (MG) with local information was proposed to solve these problems.Based on the model,a congestion control algorithm was designed.The result of simulation indicates that the proposed algorithm has good performance on link utilization and fairness of RTT flow in multi-bottleneck network.